Festivals in Taiwan - Chong, Yu Phing (Taiwan : Goang Jiann Enterprises Corporation)
Joys of the people from generation to generation - China has been primarily an agricultural nation. Thus it is no wonder that the lunar calendar bulks large in Chinese folk customs, beliefs and festivals
Editor, Chen Yeh Ji; executive producer, Jason Chu and Chong Tzu-Chiang
Narrator : Paul Niddor
Keywords: Festivals; Taiwan